Түмэн мэсийн гэгээнтний дээд таалал оршихуй - Б.Хишигсүх; Д.Галбаатар (Acta Mongolica, 2013)
Fifth reincarnation ofNoyon Hutagt. Danzanravjaa, who was enlightened having deep cognizance on secret oflife and various behaviors of human world and then back to normal human life. Based on his importunate exploring of many folk stories, facts and cites by scientists and witnesses that were inherited in both oral and written, he revealed his unique destiny from reaching clandestine fetich and adoration ofsaint to a normal human life in his novel "Saint'*7 **Gegeenten** and had expressed real facts in highly artistic manner.